Circulating immune complexes in children with rheumatic fever - Sarıkayalar, Fikriye; Bakkaloğlu, Ayşın (The Turkish Journal of Pediatrics, 1988)
The circulating immune complexes in rheumatic fever patients with various clinical presentations were investigated by the Raji-cell radioimmunoassay technique. The Jones Criteria was used for guidance in the diagnosis of 38 rheumatic fever patients and 13 age-matched healthy controls. Immune complexes were found to be strongly positive in 27 (71%) of the 38 rheumatic fever patients. Immune complexes were positive in 13 (81.2%) of 16 patients with acute rheumatic fever carditis, in four (50%) of the eight patients with acute rheumatic fever without carditis, in six (66.6%) of the nine patients with inactive rheumatic fever with valvular diseases, in four (80%) of the five patients with rheumatic chorea and in one (7.6%) of the 13 controls. The presence of circulating immune complexes in patients with rheumatic fever may be responsible for the severity of the clinical presentation and the duration of the disease.